Tingkat Kepuasan Konsumen Di Balai Laboratorium Kesehatan Provinsi Kalimantan Tengah Tahun 2015 - Nurhalina Nurhalina; Andris Dadang; Riska Gustinawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The Central Health Laboratory (BLK) of Central Kalimantan Province is the only one health laboratory referral center in Central Kalimantan Province. Therefore in carrying out their duties and functions they are always directed to meet the standards defined service. Observation results show that in 2014 the amount Consumer visits at the BLK decreased by a relative 10% compared to years previous. Based on the opinion of experts, that customer satisfaction is one factor that influences the number of consumer visits to a service center. Aim this research is describing the level of customer satisfaction based on indicators of Tangible, competency, courtesy, security, and accessibility indicators. This study uses an observational study design with a survey approach. The population is all consumers of the Central Kalimantan Provincial Health Laboratory Center in 2015, while samples were consumers who visited the BLK at the time research is underway. Sampling withdrawal technique uses Accidental Sampling method and data were analyzed univariately. The results showed that the level of customer satisfaction with appearance BLK physicality is 3.12, competence (3.23), politeness (3.22),) ease of access (3.15), security (3.26). So that the average level of satisfaction of BLK Province consumers is obtained Central Kalimantan in 2015 was 3.20 at an interval of 79.92 which means quality the service of the Central Kalimantan Health Laboratory Center reached the category